2019
DOI: 10.1186/s12014-019-9256-y
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ and PRM-based quantitative proteomics in early recurrent spontaneous abortion: biomarkers discovery

Abstract: Background Early recurrent spontaneous abortion (ERSA) is a common condition in pregnant women. To prevent ERSA is necessary to look for abortion indicators, such as hormones and proteins, in an early stage. Methods Thirty patients with ERSA were enrolled in the case group. In the control group, we recruited 30 healthy women without a history of miscarriage undergoing voluntary pregnancy termination. The differentially expressed prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The PRM results were analyzed with Skyline quantitative analysis [43]. The expression of target proteins was obtained in the sample with the corrected internal standard peptide signal [44]. [46].…”
Section: Target Analysis By Parallel Reaction Monitoring (Prm)mentioning
confidence: 99%
“…The PRM results were analyzed with Skyline quantitative analysis [43]. The expression of target proteins was obtained in the sample with the corrected internal standard peptide signal [44]. [46].…”
Section: Target Analysis By Parallel Reaction Monitoring (Prm)mentioning
confidence: 99%
“…[19][20][21][22][23] Some signal amplification strategies based on RCA have been applied to achieve sensitive detection of markers at low levels. [24][25][26][27] Proteins are the key markers of disease, [28][29][30][31] therefore the development of highly sensitive methods to detect protein markers is a promising direction for disease. This paper reviews protein detection based on RCA using for example fluorescence [32] and electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent spontaneous abortion (RSA) is a common gynecological disease in China, de ned by two or more failed pregnancies, its etiology remains unclear, genetics, autoimmune abnormalities, endocrine, anatomy, or pre-thrombotic state are thought to be related to its pathogenesis [15,16]. Previous proteomic study had shown that there is a signi cant changes occurred in the pathway of Fc gamma R-mediated phagocytosis in RSA, this result indicated that autoimmunity is invloved in its pathogenesis [17]. A study suggested that RSA may be caused by an imbalance of vaginal ora (especially that of Pseudomonas) in RSA patients [18].…”
Section: Introductionmentioning
confidence: 99%